Motivation as a Driver of Customer Service: The Impact on Automobile Dealerships - Escamilla, Roxana Dalila; Segovia-Romo, Adriana; Terán Cázares, Maria Mayela (Mercados y Negocios, 2022)
The objective of the research is to analyze the relationship of Motivation as a soft skill that drives Customer Service in car dealerships, specifically in sales area employees. The survey was applied to a sample of 81 managers from the sales area of automotive agencies in the Monterrey metropolitan area. The proposed model was linear regression. The surveys were processed with SPSS Statistics. The hypothesis was confirmed about the positive and significant relationship of the predictor variable and the dependent variable in the employees of the sales area in the automobile agencies. It is suggested to analyze and build a complementary profile of the necessary soft skills of sales collaborators in car dealerships and other sectors.